Cascades of violence : war, crime and peacebuilding across South Asia - Braithwaite, John; D'Costa, Bina (Peacebuilding compared., 2018)
War and crime are cascade phenomena. War cascades across space and time to more war; crime to more crime; crime cascades to war; and war to crime. As a result, war and crime become complex phenomena. That does not mean we cannot understand how to prevent crime and war simultaneously. This book shows, for example, how a cascade analysis leads to an understanding of how refugee camps are nodes of both targeted attack and targeted recruitment into violence. Hence, humanitarian prevention also must target such nodes of risk. This book shows how nonviolence and nondomination can also be made to cascade, shunting cascades of violence into reverse. Complexity theory implies a conclusion that the pursuit of strategies for preventing crime and war is less important than understanding meta strategies. These are meta strategies for how to sequence and escalate many redundant prevention strategies. These themes were explored across seven South Asian societies during eight years of fieldwork.